Measuring trainee competence in performing endoscopic retrograde cholangiopancreatography: A systematic review of the literature. Issue 2 (March 2019) - Voiosu, Theodor; Bălănescu, Paul; Voiosu, Andrei; Benguş, Andreea; Preda, Carmen; Umans, Devica S; Bogdan Mateescu, Radu; van Hooft, Jeanin E
Background: Current recommendations on training in endoscopic retrograde cholangiopancreatography are predicated on a performance-centred approach designed to ensure that trainees achieve appropriate skills. We aimed to analyse how competence in endoscopic retrograde cholangiopancreatography is defined in the literature and what proportion of trainees actually reach this threshold. Methods: We conducted a systematic MEDLINE search for studies reporting on endoscopic retrograde cholangiopancreatography training programmes in a clinical setting. The main outcome measure was threshold for achieving competence in endoscopic retrograde cholangiopancreatography; the secondary outcome measure was assessment of trainee performance. Quality was assessed using the Cochrane Risk of Bias tool and the Methodological Index for Non-Randomized Studies criteria. Results: Of 522 initially identified articles, 20 were included in the analysis; most studies showed a high risk of bias. Cannulation rate of the desired duct was the main marker of competence in all studies; however, only 8/20 studies reported on the performance of individual trainees, who achieved their respective standard of competence in only 25.6% of reported cases. Conclusions: Current literature identifies cannulation rate of a native papilla to be the most appropriate measure of endoscopic retrograde cholangiopancreatography competence; however, most trainees do not reach predefined competence thresholds. Furthermore, due to the limitations of available studies, the most appropriate competence measure remains subject for debate.